Analisis Semantik Lafadz Basyar, Insān, Nās, dan Banī Ādam dalam Al-Qur'an: Perspektif Ulama Klasik dan Kontemporer serta Implikasinya terhadap Pendidikan Islam - Lelah Nurjamilah; Jaenal Mutaqin; Badruzaman M. Yunus; Endi Suhendi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
The Qur'an al-Karīm employs at least four principal terms in referring to human beings, namely al-basyar, al-insān, al-nās, and banī Ādam. These terms are not merely synonymous; rather, each represents distinct yet complementary dimensions of humanity in constructing a holistic concept of the human being. This study aims to: (1) analyze the semantic meanings of these four terms based on mufrodat studies, Makkiyah-Madaniyah classification, and asbābun nuzūl; (2) compare the interpretations of classical scholars - Al-Ṭabarī, Ibn Kathīr, Al-Qurṭubī, and Fakhr Al-Rāzī - with those of contemporary scholars - Sayyid Quṭb, Ibn ‘Āshūr, M. Quraish Shihab, and Buya Hamka; and (3) formulate their implications for Islamic education. This research employs a library research method using the tafsīr maudhū‘ī approach integrated with Izutsu’s semantic analysis model. The findings reveal that al-basyar represents the physical-biological dimension of human beings; al-insān represents the spiritual dimension in relation to ‘ubūdiyyah toward Allah; al-nās represents the social-collective dimension; and banī Ādam represents the intellectual-rational dimension inherited from Adam through the divine gift of teaching al-asmā’ (Qur'an 2:31). Collectively, these four dimensions provide fundamental implications for the development of objectives, curriculum, methodology, and evaluation within holistic and comprehensive Islamic education.